Describing food safety perceptions among growers and vendors in Cambodian informal vegetable markets - Mosimann, Sabrina; Ouk, Keorimy; Bello, Nora M.; Chhoeun, Malyheng; Thompson, Leah; Vipham, Jessie; Hok, Lyda; Ebner, Paul (Frontiers in Sustainable Food Systems, 2023)
To inform the design of food safety programs in Cambodia, this study measured perceptions of vegetable safety among vegetable growers (n = 69; Battambang, Siem Reap) and vendors (n = 31; Phnom Penh) involved in Cambodian informal vegetable markets. The majority of respondents (≥ 62.7%, lower bounds of 95% confidence intervals at least 46.2%) across all groups (growers and vendors) were at least “moderately concerned” (scale: “extremely concerned”, “moderately concerned”, “slightly concerned”, “not concerned at all”) about the safety of vegetables sold in Cambodia. However, the mean estimated probability of respondents reporting that chemical contamination was of greater concern than microbial contamination was 84.9% [76.0, 90.9]%. Most respondents reported familiarity with the health effects of consuming chemically (71.4% [61.5, 79.6]%) or microbially (57.3% [47.2, 66.9]%) contaminated vegetables. However, less than half (between 7.3% and 48.4%) of all respondents provided a commonly recognized example of such health effects. Respondents most frequently perceived contamination of vegetables as occurring “at the farm” (≥ 76.7%, lower bounds of 95% confidence intervals at least 61.5%, and ≥ 39.3%, lower bounds of 95% confidence intervals at least 21.2%, respectively). Additionally, most respondents (≥ 51.6%, lower bounds of 95% confidence intervals at least 34.0%) perceived “vegetable farmers” as responsible for preventing chemical contamination. Perceptions of responsibility for preventing microbial contamination varied across groups (p = .02). Of the vendors in Phnom Penh, growers in Battambang, and growers in Siem Reap, 22.6%, 39.0%, and 53.6%, respectively, described at least one commonly accepted contamination prevention practice. These results suggest that food safety programs for the described groups should aim to increase understanding of the health impacts of consuming contaminated vegetables. However, specific emphasis should be placed on increasing awareness on the health impacts of consuming vegetables contaminated with microbial pathogens as respondents were generally less aware and concerned with microbial vs. chemical contamination of vegetables. Additionally, programs targeting vegetable growers could leverage growers’ sense of personal responsibility for both contamination and contamination prevention, while programs for vegetable vendors may need to emphasize the importance of vendors in ensuring vegetable safety.